Analysis of cardiovascular surgery specialization theses and their publication rates - Omer Faruk Rahman; Mustafa Baris Kemahli; Fevzi Ayyildiz (Turkish Journal of Vascular Surgery)
Aim: This study aimed to analyze the specialization theses in the field of cardiovascular surgery in Turkiye, and examine their rates of conversion to scientific publications. Material and Methods: Specialization in medicine theses in the field of cardiovascular surgery published in Turkiye from 2015 to 2020 were evaluated using the Council of Higher Education Thesis Center database. For each specialization thesis, details such as the year, institution, city, study design, advisor's title, and author information were recorded. The conversion of theses into scientific publications was assessed using Google Scholar, PubMed, Dergipark, and TR Index databases based on the thesis title, advisor, and author information. Results: A total of 204 specialization theses in medicine were examined in the study. Of the thesis authors, 171 were men (83.3%) and 33 were women (16.2%). When categorized by institutions, 130 theses (63.7%) were affiliated with institutions in the three major cities. It was observed that 79 of the evaluated theses (38.7%) were turned into scientific publications. The conversion rate into scientific publications was significantly higher in institutions affiliated with the University of Health Sciences (p=0.002). A significant relationship was observed between the study design, the index of the publishing journal, and the citation status (p=0.029, p [Turk J Vasc Surg 2024; 33(3.000): 132-8]